Legal Counseling as a Preventive Effort to Prevent Juvenile Delinquency at Three Language High School (SBTH) Magelang - Noviasari, Dilli Trisna; Oktavia, Nadhifa Nur; Akhrama, Nasa; As-Sidiqi, Muhammad Hasbi (Universitas Muhammadiyah Magelang, 2025)
Juvenile delinquency is a social problem that often occurs among school students. One form of prevention of juvenile delinquency in schools is through legal counseling activities. Legal counseling activities at SMA Tiga Bahasa (SBTH) Magelang aim to provide insight to school children about the dangers of juvenile delinquency. This counseling activity is expected to increase legal understanding from an early age to school children so that students are able to recognize the legal consequences and social impacts of any deviant behavior. The methods used in this activity are legal counseling and questions and answers with students regarding the abuse of narcotics, alcohol, psychotropics, and addictive substances (NAPZA), bullying, and the misuse of sharp weapons. Thus, with this legal counseling, the result show that students of SMA Tiga Bahasa (SBTH) Magelang can develop a sense of discipline and responsibility, and play an active role in creating a safe, orderly, and conducive school environment. This activity is also a preventive effort to reduce the number of juvenile delinquency and support the formation of a young generation that is aware of the law and has a positive character.